PROTOTYPE PENGONTROL PENGISIAN TANDON AIR SECARA PARALEL MENGGUNAKAN SOLENOID VALVE BERBASIS ATMEGA 2560 - La Raufun, La Raufun; Ardiansyah, Sandi (JURNAL INFORMATIKA, 2018)
Water has an important role in the survival of living things on earth. Humans use water for various needs, in the household for example for consumption, bathing, washing and so on. In using water it is necessary to save both the use and filling, this needs a filling controller so that the water does not overflow. The purpose of this study is to design a controller to replenish water reservoirs that can help or facilitate humans in controlling water filling in several reservoirs and can prevent water overflow in reservoirs. In the design of this tool uses Arduino Mega 2560 as a data processor and water float sensor as an input water level detector and a DC water pump, relay and solenoid valve as the output. With the design of this tool it can fill water reservoirs automatically and will stop filling water thereby preventing the overflow of water in the water reservoir.Keywords: Microcontroller, Solenoid Valve, Water reservoir and Water Float